Evaluation of a nasal surgical questionnaire designed for monitoring surgical outcomes and comparing different techniques. Issue 7 (July 2015) - Haye, R; Døsen, L K; Shiryaeva, O; Amlie, E
Abstract Objective: This study evaluated a nasal surgical questionnaire designed for monitoring surgical outcomes and comparing different techniques. Methods: Eighty-three healthy volunteers answered the same questionnaire twice with a minimum interval of five weeks. Three visual analogue scale items were used to assess nasal obstruction during the day, at night and during exercise. Respondents rated nasal obstruction severity by marking on a 10 cm line, with scores ranging from 0 to 100 (measured in millimetres). Other nasal symptoms, considered secondary outcomes, were graded using four-point Likert scales. Results: Mean visual analogue scale scores for nasal obstruction severity experienced during the day, at night and during exercise at initial assessment were 9.99, 12.95 and 11.67, respectively. Thirty-eight per cent of scores indicated no obstruction (scores of 0), 47 per cent indicated mild obstruction (scores 1–30), 13 per cent indicated moderate obstruction (scores 31–70) and 2 per cent indicated severe obstruction (scores 71–100). Males had higher scores than females. The scores for the first and second assessment did not differ, except at night for obstruction in allergic individuals which was considered clinically unimportant. Conclusion: The questionnaire reliably assesses nasal symptoms and may be useful for prospective studies of nasal surgery.